1-methylnaphthalene LIF: Extension of the calibration data basis for temperature and concentration measurements - Zigan, Lars; Lind, Susanne; Aßmann, Simon; Will, Stefan (18th Gordon Research Conference on Laser Diagnostics in Combustion, 2015)

A Mobile Device for Nanoparticle Characterization by Wide-Angle Light Scattering (WALS) and Laser-Induced Incandescence (LII) - Aßmann, Simon; Huber, Franz; Will, Stefan (8th World Congress on Particle Technology, 2018)

An optimized evaluation strategy for a comprehensive morphological soot nanoparticle aggregate characterization by electron microscopy - Altenhoff, Michael; Aßmann, Simon; Teige, Christian; Huber, Franz; Will, Stefan (Journal of Aerosol Science, 2020)
For a comprehensive understanding of nanoparticle formation in gas phase processes, such as soot formation, morphological parameters of fractal-like particle aggregates, like the radius of gyration, the fractal dimension and the primary particle size, have to be determined. Often transmission electron microscopy (TEM) is employed for the investigation of particle characteristics as it not only allows to investigate ensemble averages but single particle aggregates and thus also to determine statistical properties, such as the size distribution within a sample. Many different evaluation methods can be found in the literature. We investigated different approaches for the determination of morphological parameters from TEM images of soot and compared the results to derive an optimized evaluation strategy for TEM nanoparticle characterization. We compared four methods for the determination of the radius of gyration – three length- and one pixel-based methods – showing good agreement within 9% deviation for the median of the recovered lognormal size distribution. Furthermore, the fractal dimension was determined via a sample-based and various box counting methods with different limiting box sizes. Here, we could show that the upper and lower bounds (aggregate size in terms of radius of gyration and primary particle size in terms of its radius, respectively) of self-similarity of fractal-like aggregates should be accounted for by choosing corresponding upper and lower box sizes. Using box counting, we could show that for small aggregates the fractal dimension as well as its span are increased, yet with increasing aggregate size the fractal dimension converges towards 1.6. Furthermore, we could show the potential of semi-automatic aggregate detection through Trainable Weka Segmentation. However, image noise resulting in erroneous aggregate splitting often leads to smaller aggregate sizes by automatic detection compared to manual segmentation. Generalized Hough Transformation for the semi-automatic determination of primary particle sizes performs well for large soot particle aggregates as those often show spherical primary particles. For leaner combustion conditions, the primary particles of the formed clumpy soot aggregates cannot be detected well via semi-automatic detection. TEM images were taken on soot samples from premixed laminar flat flames (burner type: McKenna) under various conditions to provide comprehensive reference data.
CRIS-Team Scopus Importer:2019-11-01
Keywords: Fractal dimension; McKenna flame; Nanoparticle aggregates; Radius of gyration; Soot; TEM; Transmission electron microscopy

Characterisation of the transition type in optical band gap analysis of in-flame soot - Bauer, Florian; Bräuer, Phillipp; Aßmann, Simon; Thiele, Maximilian A.; Huber, Franz; Will, Stefan (Combustion and Flame, 2022)
Semiconductor materials are characterised by a band gap between conduction and valence band, which can either be of direct or indirect nature depending on the crystal momentum. In case of applying the so-called Tauc method to infer the band gap value, both transition types are described by different values for the transition type exponent. In the case of soot particles, the optical band gap is an important quantity during the evolution process to describe the optical characteristics mainly linked to the underlying structural properties. In this work, an approach to infer the optical band gap value together with the transition type exponent is used to shed light on the electronic nature and optical properties of soot during its formation process. In situ UV–Vis-NIR extinction measurements as well as ex situ Raman spectroscopy are performed in a non-premixed ethylene/air flame at two different positions in the flame reflecting different stages of the soot formation process. The results reveal two important tendencies: first, an increase in the band gap energy of young soot is observed, possibly caused by the curvature of initially planar polycyclic aromatic hydrocarbon monomers due to the presence of odd-numbered rings in the hexagonal aromatic lattice. Second, a decrease of the transition type exponent value can be observed, indicating a shift from an indirect transition to a more direct band structure. Further, the indirect band gap assumption for mature soot and its band gap value close to 0.2 eV can be confirmed experimentally. The Raman results provide additional insight in the atomic fine structure of the soot particles regarding the defect density and the loss of amorphous character with increasing maturity.
CRIS-Team Scopus Importer:2022-01-28
Keywords: Raman spectroscopy; Soot band gap energy; Soot formation; Tauc method; Transition type

Characterization of Soot Aggregates in Premixed Flat Flames by a Combination of Two-Dimensional Multi-Angle Light Scattering (2D-MALS) and Laser-Induced Incandescence (LII) - Altenhoff, Michael; Aßmann, Simon; Huber, Franz; Will, Stefan (36th International Symposium on Combustion, 2016)

Characterization of the phosphor (Sr,Ca)SiAlN3: Eu2+ for temperature sensing - Hertle, Ellen Elisabeth; Bollmann, Jonas; Aßmann, Simon; Kalancha, Violetta; Osvet, Andres; Batentschuk, Miroslaw; Will, Stefan; Zigan, Lars (Journal of Luminescence, 2020)
Laser-induced phosphorescence based on luminescent particles is a suitable technique for remote temperature sensing. The luminescence characteristics of the phosphor (Sr,Ca)SiAlN3:Eu2+ (”SCASN”) were investigated regarding the suitability of the material for phosphor thermometry. The phosphor has a high quantum efficiency, a very broad excitation band, an emission peak centered at about 620 nm and a short lifetime of less than 1μs, which makes it promising for thermometry measurements. After excitation at 532 nm, the luminescence emission reveals a blue shift with increasing temperature, which can be used for temperature calibration based on the two-color intensity ratio method. The excitation and emission characteristics are favorable for measurements in environments containing fuels and oils, which tend to fluorescence after UV-excitation. The phosphor allows for measurements up to 800 K, with a quenching temperature of 530 K. Spectral characteristics are presented for both bulk powder and a surface coating. For the former, a significant shift in the position of the emission peak is observed, which is most probably due to distinct re-absorption. A change in excitation laser fluence slightly affected the luminescence emission spectrum of both bulk material and coating and thus requires consideration in temperature determination.
CRIS-Team Scopus Importer:2020-06-30
Keywords: Optical sensor; Phosphor thermometry; SCASN

Charakterisierung von Pulvern im Nanobereich - Aßmann, Simon; Huber, Franz; Will, Stefan (Powtech Networking Campus, 2019)

Comprehensive characterization of nano-aerosols by Wide-Angle Light Scattering (WALS) and Laser-Induced Incandescence (LII) - Aßmann, Simon; Huber, Franz; Will, Stefan (PARTEC: International Congress on Particle Technology, 2019)

Comprehensive morphological characterization of industrial nano-aerosols by optical measurement methods - Aßmann, Simon; Bauer, Florian; Huber, Franz; Will, Stefan (International Conference on Advanced Optical Technologies, 2019)

Comprehensive Online-Characterisation of Nanoparticles by Wide-Angle Light Scattering and Laser-Induced Incandescence - Huber, Franz; Aßmann, Simon; Will, Stefan (Sensors Day 2017, 2017)

Determination of droplet size from wide-angle light scattering image data using convolutional neural networks - Kirstein, Tom; Aßmann, Simon; Furat, Orkun; Will, Stefan; Schmidt, Volker (Machine Learning: Science and Technology, 2024)
Wide-angle light scattering (WALS) offers the possibility of a highly temporally and spatially resolved measurement of droplets in spray-based methods for nanoparticle synthesis. The size of these droplets is a critical variable affecting the final properties of synthesized materials such as hetero-aggregates. However, conventional methods for determining droplet sizes from WALS image data are labor-intensive and may introduce biases, particularly when applied to complex systems like spray flame synthesis. To address these challenges, we introduce a fully automatic machine learning-based approach that employs convolutional neural networks (CNNs) in order to streamline the droplet sizing process. This CNN-based methodology offers further advantages: it requires few manual labels and can utilize transfer learning, making it a promising alternative to conventional methods, specifically with respect to efficiency. To evaluate the performance of our machine learning models, we consider WALS data from an ethanol spray flame process at various heights above burner surface, where the models are trained and cross-validated on a large dataset comprising nearly 35000 WALS images.
CRIS-Team Scopus Importer:2024-04-12
Keywords: convolutional neural network; hetero-aggregate; inverse problem; machine learning; nanoparticle synthesis; spray flame synthesis; WALS imaging

Droplet sizing in spray flame synthesis using wide-angle light scattering (WALS) - Aßmann, Simon; Münsterjohann, Bettina; Huber, Franz; Will, Stefan (Applied Physics B-Lasers and Optics, 2020)
In spray flame synthesis the processes of spray formation and evaporation of the single droplets greatly affect the morphology and size of particles formed. An in situ measurement of these parameters is thus essential for process control and development. In this work, wide-angle light scattering (WALS) is applied to measure droplet sizes in a spray flame. The scattering data of the spherical droplets are evaluated by applying Mie-theory. For droplet sizing, the number of characteristic maxima in the scattering pattern and the measured scattering intensities are evaluated. Droplet size distributions and their parameters were determined by repetitive exposures in various heights above the nozzle outlet for two solvents: pure ethanol and a mixture of ethanol and 2-ethylhexanoic acid at a volume ratio of 35/65. While for ethanol the median droplet size decreases with increasing height, it decreases less for the mixture, which in general exhibits increased droplet sizes for all heights compared to pure ethanol. Furthermore, we could show that using air instead of nitrogen as a co-flow barely affects droplet evaporation in the flame.
CRIS-Team Scopus Importer:2020-05-08

Einsatz der Weitwinkel-Lichtstreuung zur Bestimmung der Tropfengrößenverteilung und Partikelmorphologie in der Sprayflammensynthese - Aßmann, Simon; Münsterjohann, Bettina; Huber, Franz; Will, Stefan (Jahrestreffen der Processnet-Fachgruppen Partikelmesstechnik und Aerosoltechnologie, 2019)

Fluorescence characteristics of the fuel tracers triethylamine and trimethylamine for the investigation of fuel distribution in internal combustion engines. - Will, Stefan; Aßmann, Simon; Lind, Susanne; Zigan, Lars (Applied Optics, 2016)
Laser-induced fluorescence based on fuel tracers like amines is a suitable measurement technique for mixing studies in internal combustion (IC) engines. Triethylamine has often been used in gasoline IC engines; however, no detailed fluorescence characterization for excitation at 263 or 266 nm is available. Trimethylamine (TMA) exhibits high potential as a gaseous fuel tracer but little information about TMA fluorescence is currently available. A picosecond laser source combined with a streak camera equipped with a spectrograph was used to determine the spectral fluorescence emission and fluorescence decay time of both tracers. The tracers were investigated at various temperatures and pressures in a calibration cell with nitrogen as bath gas. The results provide an in-depth understanding of the fluorescence characteristics of both tracers and allow assessment of their application to the investigation of fuel distribution in IC engines.

In situ characterization of particle formation in spray flame synthesis using wide-angle light scattering - Aßmann, Simon; Huber, Franz; Will, Stefan (Particuology, 2024)
Wide-angle light scattering (WALS) was used for in situ measurements of droplet and nanoparticle size distributions during the synthesis of titania and iron oxide particles from liquid precursor solutions in the standardized SpraySyn burner for spray flame synthesis. Titania was synthesized from titanium tetraisopropoxide (TTIP) and iron oxide from iron(III) nitrate nonahydrate (INN) using ethanol (EtOH) as solvent. Scattering images were taken at heights up to 120 mm above the burner surface and classified into droplet and particle scattering. Droplet size distributions were derived from a sequential analysis of scattering data containing the oscillating Mie pattern, the lognormal size distribution parameters for spherical and fractal particle fractions from a multivariate approach on averaged particle scattering data. The results show that the precursor addition leads to altered evaporation behavior and even droplet disruption probably induced by puffing or micro-explosions compared to pure EtOH. In the case of TTIP (a hygroscopic alkoxide), the synthesis of a large fraction of spheres was observed, while the nitrate INN leads to the formation of mostly fractal aggregates.
CRIS-Team Scopus Importer:2024-04-05
Keywords: Droplet size distribution; Elastic light scattering; Metal oxide particles; Nanoparticle morphology; Particle size distribution; Spray flame synthesis

In Situ Determination of Droplet and Nanoparticle Size Distributions in Spray Flame Synthesis by Wide-Angle Light Scattering (WALS) - Aßmann, Simon; Münsterjohann, Bettina; Huber, Franz; Will, Stefan (Materials, 2021)
The investigation of droplet and nanoparticle formation in spray flame synthesis requires sophisticated measurement techniques, as often both are present simultaneously. Here, wide-angle light scattering (WALS) was applied to determine droplet and nanoparticle size distributions in spray flames from a standardized liquid-fed burner setup. Solvents of pure ethanol and a mixture of ethanol and titanium isopropoxide, incepting nanoparticle synthesis, were investigated. A novel method for the evaluation of scattering data from droplets between 2 µm and 50 µm was successfully implemented. Applying this, we could reveal the development of a bimodal droplet size distribution for the solvent/precursor system, probably induced by droplet micro-explosions. To determine nanoparticle size distributions, an appropriate filter and the averaging of single-shot data were applied to ensure scattering from a significant amount of nanoparticles homogeneously distributed in the measurement volume. From the multivariate analysis of the scattering data, the presence of spherical particles and fractal aggregates was derived, which was confirmed by analysis of trans-mission electron microscopy images. Monte Carlo simulations allowed determining the distribution parameters for both morphological fractions in three heights above the burner. The results showed relatively wide size distributions, especially for the spherical fraction, and indicated an ongoing sintering, from fractal to spherical particles.
CRIS-Team Scopus Importer:2021-11-26
Keywords: Droplet size distribution; Elastic light scattering; Flame spray pyrolysis; Fractal aggregates; Multivariate data analysis; Particle size distribution; Spherical particles; Spray flame synthesis; TiO; Wide-angle light scattering

Investigation of soot formation in 2D by combined multi-angle light scattering and laser-induced incandesence employing a shielding approach - Aßmann, Simon; Altenhoff, Michael; Perlitz, Julian; Bauer, Florian; Huber, Franz; Will, Stefan (8th International Workshop on Laser Induced Incandescence, 2018)

Kombination von zweidimensionaler Multi-Winkel-Lichtstreuung und Laserinduzierter Inkandeszenz zur morphologischen Charakterisierung von Rußpartikeln in Flammen - Aßmann, Simon; Altenhoff, Michael; Huber, Franz; Will, Stefan (Jahrestreffen der ProcessNet-Fachgruppe Partikelmesstechnik, 2017)

Laseroptische Charakterisierung der Primärpartikelgröße und Volumenkonzentration von Furnaceruß unter variierenden Prozessbedingungen - Aßmann, Simon; Huber, Franz; Will, Stefan (Jahrestreffen der ProcessNet-Fachgruppe Partikelmesstechnik, 2019)

Online-Aerosolcharakterisierung durch Kombination der Weitwinkel-Lichtstreuung und Laserinduzierten Inkandeszenz - Huber, Franz; Aßmann, Simon; Will, Stefan (Jahrestreffen der ProcessNet-Fachgruppe Gasreinigung und des TAK Aerosoltechnik, 2018)

Optical investigation of particle characteristics produced by Spray Flame Synthesis using Wide-Angle Light-Scattering (WALS - Münsterjohann, Bettina; Aßmann, Simon; Huber, Franz; Will, Stefan (PARTEC, 2019)

Simultane Charakterisierung der Spray- und Partikelbildung in der Sprühflammensynthese mittels Weitwinkel-Lichtstreuung - Aßmann, Simon; Münsterjohann, Bettina; Huber, Franz; Will, Stefan (Jahrestreffen 2021 der ProcessNet-Fachgruppen „Gasreinigung“ und „Partikelmesstechnik", 2021)

Simultaneous characterization of droplet size distributions and particle morphology in spray flame synthesis by wide-angle light scattering (WALS) - Aßmann, Simon; Münsterjohann, Bettina; Huber, Franz; Will, Stefan (4th International Symposium Gas‐Phase Synthesis of Functional Nanomaterials: Fundamental Understanding, Modeling and Simulation, Diagnostics, Scale‐up and Application, 2020)

Soot aggregate sizing in an extended premixed flame by high-resolution two-dimensional multi-angle light scattering (2D-MALS) - Altenhoff, Michael; Aßmann, Simon; Perlitz, Julian; Huber, Franz; Will, Stefan (Applied Physics B-Lasers and Optics, 2019)
The spatial distribution of soot aggregate size and morphology within a premixed flat flame (McKenna-type burner and ethyne-air mixture at an equivalence ratio of phi = 2.7) is characterized by two-dimensional multi-angle light scattering (2D-MALS). A profound investigation of such an extended, radially symmetrical sooting flame with 2D-MALS requires a sophisticated camera calibration to correct for non-linear image scaling and a careful evaluation of the scattering data. Sharp scattering images were acquired in the angular range from 20 degrees to 155 degrees using a rotatable camera system and an automated Scheimpflug adapter. To correct for non-linear variations in horizontal and vertical image magnification occurring at scattering angles differing from perpendicular view, a polynomial-based image transformation algorithm was developed to convert all scattering images into a common coordinate system. Effective radii of gyration and fractal dimensions of soot aggregates were then derived from scattering data by two different approaches. Due to limited amount of angular positions, the classical method based on Guinier and power law analysis shows limitations, as it yields discontinuous results, predominantly in axial direction of the burner. Bayesian analysis was then used for a data fit of the complete structure factor conducting a least square minimization leading to more consistent results. The use of prior knowledge in the Bayesian evaluation allows for improved data fitting and reduced uncertainties in radius of gyration and fractal dimension even for small aggregate sizes.
CRIS-Team WoS Importer:2019-09-17

Spray and Particle Characterization of a Spray Flame Synthesis Process using Wide-Angle Light Scattering (WALS) - Münsterjohann, Bettina; Aßmann, Simon; Huber, Franz; Will, Stefan (Proceedings of the Proceedings 9th European Combustion Meeting (ECM 2019), 2019)
Spray Flame Synthesis (SFS) is a promising technology to produce nanomaterials with well-defined functional properties. Since particle size and morphology have a significant influence on the properties of the synthesized nanoparticles, correlations between these parameters, the droplet size of the spray and process conditions are required. For this reason, Wide-Angle Light Scattering (WALS) is applied to a flame of a standardized SFS burner, which allows for both droplet and particle size evaluation. For the aggregate size Rg,eff, no significant influence of different dispersion gas flow rates on particle morphology is measured, while the droplet size d decreases with increasing dispersion gas flow rate

Two-Dimensional Soot Particle Sizing by a Combination of Multi-Angle Light Scattering (2D-MALS) and Laser-Induced Incandescence (2D-LII) - Altenhoff, Michael; Aßmann, Simon; Huber, Franz; Will, Stefan (7th International Workshop on Laser Induced Incandescence, 2016)

Two-Dimensional Soot-Particle Sizing in a Premixed Flat-Flame by a Combination of Multi-Angle Light Scattering and Laser-Induced Incandescence - Aßmann, Simon; Altenhoff, Michael; Perlitz, Julian; Huber, Franz; Will, Stefan (Gordon Research Conference on Laser Diagnostics in Combustion, 2017)

Umfassende Charakterisierung von Nanopartikeln unter Einsatz der Weitwinkel-Lichtstreuung und der Laserinduzierten Inkandeszenz - Aßmann, Simon; Huber, Franz; Will, Stefan (Jahrestreffen der ProcessNet-Fachgruppe Partikelmesstechnik, 2018)

Umfassende morphologische Charakterisierung von industriellen Nano-Aerosolen durch optische Messverfahren - Aßmann, Simon; Huber, Franz; Will, Stefan (Jahrestreffen der ProcessNet-Fachgruppe Partikelmesstechnik und des Arbeitsausschusses Feinstäube, 2020)

Vergleich von Verfahren zur Charakterisierung von Aerosolen an einem Stoffsystem mit variierbarer Partikelform - Hillemann, Lars; Babick, Frank; Stintz, Michael; Seipenbusch, Martin; Aßmann, Simon; Huber, Franz; Kiesler, Dennis; Kruis, E; Pitz, M.; Antonyuk, S; Friehmelt, R; Sachweh, B; et al. (Jahrestreffen der ProcessNet-Fachgruppe Partikelmesstechnik, 2018)

Wide-Angle Light Scattering for droplet and particle analysis in a Spray Flame Synthesis process - Münsterjohann, Bettina; Aßmann, Simon; Huber, Franz; Will, Stefan (International Conference on Advanced Optical Technologies, 2019)